Emotions towards two national minority languages in Sweden : Insights from language heritage communities - Brännmark, Theres; Toropainen, Outi (De Gruyter Mouton, 2026)
This article explores the lived experiences of participants with heritage language background in Norrbotten County, Northern Sweden, with regard to two national minority languages – Finnish and Meänkieli. In the study, explanations of participants’ visualised and multicoloured language portraits were analysed to gain insight into the how the participants have experienced these languages and the emotions these experiences have evoked. Participants valued these languages, but felt excluded in their relationship to them, because only previous generations have had natural access to them. The loss of the language and attitudes about this loss were explained through both individual and collective experiences, such as Swedification and inadequate support. Participants expressed a vision of the future in which they could become part of the minority language community. To achieve such a future, education is essential. It can maintain and strengthen language skills and foster cooperation between informal environments and formal educational spheres. Our findings indicate that through collective action, more positive attitudes towards minority languages and fruitful education could be achieved.